Service Excellence Untuk Pemilik Bisnis Kecil Di Surabaya - Yuliasti Ika Handayani; Veronika Rahmawati; Marliana Junaedi; Monica Adjeng Erwita; Fenika Wulani (LPPM, Universitas Katolik Widya Mandala Surabaya, 2021)
The purpose of the activity with the topic of service excellence includes providing counseling and consultation regarding providing excellent service, handling customer complaints, and using technology and social media to market products. Participants in the activity are small business owners in Surabaya who generally face marketing diffi-culties during the pandemic, including technology adoption, consisten-cy in meeting certain quality standards that allow customer complaints to arise, and lack of mastery in using social media to market products and serve consumers. This activity has been held online in March 2021 in two stages. The first stage is the provision of training in 3-day session through the zoom application, which is also broadcast on the YouTube channel. The second stage is the provision of consultation for eight days through the WhatsApp Group application